A sucessão processual - Fagundes Filho, Henrique (2007)
The present thesis examines the complex problem of property´s transmission of rights in rem and contract rights to others, to whom it´s entitled the domain of the process in course, and the inheritance by the plaintiff or the defendant´s heirs. The author makes a comparison through various angles about some subjects such as historical investigation of the appearance of two types of inheritance of the rights being demanded in court, the way the problem can be solved according to the material law in the civil process, about the several solutions applied to the permeability or not of the civil process with regards to the inheritance of those rights, in private inter vivos business; comprises the so called irrelevance theory (Irelevanztheorie), the relevance theory (relevanztheorie), and the eclectic theory, also knows as the mitigated relevance theory (vermitetelnde Theorie). The author carefully examines the punctum saliens of the institute, verifies the reflex of that inheritance (inter vivos or mortis causa) and its legitimacy, considered in the scope of the civil process. After specifying the origin of what came to be called capacity , the author makes a confrontation of this institute with the ones of legitimacy and legitimation of the public, private and processual law. Since these concepts are correspondent in processual law, the author presents several understandings regarding the processual quality to the inheritance process, defining the position he believes to be the most correct one, after examining considerations that had not been properly evaluated before. The subject is dealt in the Brazilian Civil Process Code, in article 42, caput, referring to inter vivos transmission, under the expressions of alienation of rem or litigious object , corresponding to the German words die in Streit befangene Sache zu veräussern and (den geltend gemachten Anspruch). The Italian expression diritto controverso is no longer used in the Brazilian juridical system. The author, therefore, carries out a detailed study of the meaning of litigious rem and litigious object , through the German and Italian doctrines to reach a reasonable concept according to the general theory of law suit. The interest degree of the acquirer of the litigious rem or the litigious object necessarily reflects in the law suit, being subject of accurate study, providing a new doctrinal meaning thereafter. The mortis causa inheritance is the object of this present study but the highlight is due to the extension of this institute to the civil and commercial societies, its separation, association and incorporation by a third one, which according to the uniform interpretations of Italian teachers, corresponds to the term disappearance , often lent to natural people. As a conclusion, a brief summary to the problem of pendente lite, its reflexes in another form of transmission of the rem or the litigious object , knows as defraud to execution , which is now prohibited by the juridical system